Shell middens, ships and seeds: exploring coastal subsistence, maritime trade and the dispersal of domesticates in and around the ancient Arabian Peninsula - Boivin, N; Fuller, D (Springer, 2009)
The Arabian Peninsula occupies a critical position at the intersect of several major Old World landmasses. Inland aridity and a major coastal perimeter have long made maritime activities critical to Arabia’s cultural trajectory. A wealth of recent studies, not previously synthesised, suggest not only that the peninsular littoral offered a rich resource base for thousands of years of human occupation in the region, but also that Arabia witnessed some of the world’s earliest seafaring and maritime exchange activities, and played a role in Bronze Age maritime trade that has often been underestimated. Maritime activities were closely linked to developments in agriculture, which not only fuelled trade and exchange, but were also impacted on by the dispersal of domesticates along early maritime corridors. While regional specialisation has to some degree prevented consideration of the maritime prehistory of the peninsula as a whole, it is clear that there are interesting parallels, as well as important differences, between cultural trajectories in different parts of the peninsula.